Assessing Resilience to Climate Change in US Cities. (17th May 2012) - Saavedra, Casilda; Budd, William W.; Lovrich, Nicholas P.
Abstract : In the face of uncertainties associated with climate change, building adaptive capacity and resilience at the community level emerges as an essential and timely element of local planning. However, key social factors that facilitate the effective building and maintenance of urban resilience are poorly understood. Two groups of US cities differing markedly in their commitment to climate change are contrasted with respect to their planning approaches and actions related to mitigation and adaptation strategies, and also in relation to social features that are believed to enhance adaptive capacity and resilience to climate change. The first group manifests a strong commitment to climate change mitigation and adaptation, and the second group has demonstrated little or no such commitment. These cities are compared with respect to several noteworthy social features, including level of social capital, degree of unconventional thought, and level of cultural diversity. These characteristics are postulated to contribute to the adaptive capacity of communities for dealing with the impacts of climate change. The aim is to determine to what extent there is a relationship between social/cultural structures and urban commitment and planning for climate change that could discriminate between climate change resilient and nonresilient urban areas.